Challenges in Foreign Language Teaching in Iran - Amirian, Seyed Mohammad Reza; Zareian, Gholamreza (Cambridge Scholars Publishing, 2017)
This volume is a clear reflection of the realities and dynamics of language teaching in Iranian classrooms and the new trends within the Iranian EFL community over the last decade. It covers a variety of recent topics within the context of English language teaching in Iran, such as assessment and testing, Computer Assisted Language Learning (CALL), task-based methodology, and vocabulary learning, among others. The book offers readers insights into what is actually going on in language classrooms in Iran and the most effective methods, techniques and strategies to employ in promoting learning in a foreign language context.